Light-induced conical intersections for short and long laser pulses: Floquet and rotating wave approximations versus numerical exact results - Halász, Gábor J.; Cederbaum, Lorenz S. (Journal of physics. B, Atomic, molecular and optical physics, 2012)
It has recently been shown that dressing of diatomic molecules by standing or by running laser waves can give rise to the appearance of the so-called light-induced conical intersections (LICIs). The effect of these LICIs on different physical properties of the diatomic molecules has been demonstrated in several publications [1-6]. In the majority of these works, the sodium dimer was chosen as an explicit showcase example and the Floquet picture was used to describe the nuclear Hamiltonian. This representation of the Hamiltonian is very illustrative and helps to understand the essence of the light-induced nonadiabatic effects. However, the natural question arises: what are the limits of the Floquet approximation? In this paper, the performance of the 2×2 Floquet Hamiltonian in the space of the ground and resonantly excited molecular electronic states is compared to that of the time-dependent exact Hamiltonian in the same space. For the latter case, we also present results employing the popular rotating wave approximation. To carry out the comparisons, different physical properties—-autocorrelation function, excited state diabatic populations and molecular alignment—have been computed.
Gesehen am 17.05.2018